Analisis Efisiensi Takaful di Indonesia Selama Pandemi Covid-19 Dengan Menggunakan Metode Data Envelopment Analysis - Rahayu, Murtya Sri; Ruhadi, Ruhadi; Kristianingsih, Kristianingsih; Mauluddi, Hasbi Assidiki (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
One of the performance parameters that underlies all the performance of an organization or company is efficiency. This study aims to measure and determine the efficiency level of takaful in Indonesia during the Covid-19 pandemic by using the Data Envelopment Analysis (DEA) method. The DEA approach used in this study is an intermediation approach where the inputs used are total assets, operating expenses, and claim payments. While the output used is tabarru funds and investment income. This study uses 47 samples of takaful registered with OJK in 2020 and 2021. The results shows that on average takaful in Indonesia have not reached an efficient level. The inefficiency of this takaful is influenced by the use of inputs (total assets, operating expenses, and payment of claims) that are not maximized to produce optimal output.